Study on the impact of SARS-CoV 2 on the pig market at national level - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Pandemic caused by the new coronavirus has affected both farmers and the country's economy. In this study will be analyzed aspects such as: the balance of pork made in Romania (slaughter, average weight at slaughter, total production, consumption) price, pig herds, import and export. Pork is one of the most popular foods with content rich in protein, being considered a "heavy" meat with slow metabolism. It is also rich in vitamins and minerals, such as iron, magnesium, phosphorus, potassium and zinc, as well as a number of B, B6, B12 vitamins, nicotinic acid, thiamine, riboflavin. Pork contains both saturated and unsaturated fats, the muscle being framed in lean meat, and the neck and ribs in fatty meat. During the winter holidays, pork is consumed more often by the Romans and is used to prepare traditional dishes. The research method used in the study is statistical processing and economic analysis of existing data on specialized sites such as the National Institute of Statistics (INS), Eurostat, FAO, Ministry of Agriculture and Rural Development (MADR) and other specialized materials.
Keywords: Q11; Q13; L11; 330; evolution; prices; pandemic; pork